(untitled) (Oratio Directa, 2023)
The Tabuik ritual originated in Middle Eastern Shi'a traditions brought by people of Indian descent. Through agreement among nagari communities, its celebration was adapted to Minangkabau customs and developed into a Pariaman cultural tradition. This qualitative study examines the synthesis of Islam and local culture embodied in Tabuik. Its principal elements and customary values demonstrate a dynamic combination of religion and Pariaman tradition that continues to develop according to changing historical contexts.